STUDI OPTIMASI OPERASI WADUK BILI-BILI DENGAN PROGRAM DINAMIK - Riksal Firmansyah Safaa; Sri Sangkawati Sachro; Dyah Ari Wulandari (Prodi Magister Teknik Sipil Unsyiah, 2023)
Bili-Bili reservoir functions as flood control, raw water service, irrigation, river maintenance and hydropower. Every year Bili-Bili Reservoir has a reduction in storage capacity, effective storage and sediment storage, it affects the availability of water and condition of the reservoir. During the 20 years of operation, there has been a reduction in effective storage reservoir by 99,27 million m3. Likewise, sediment storage area experienced a very significant change in storage capacity in 2019 of 840 thousand m3 than design, which was 99,27 million m3. To reduced storage capacity, it is necessary to adjust reservoir operating by optimizing reservoir operating rules. Optimization model used is dynamic programming method with CSUDP software. Purpose of this study to optimize operating rule Bili-Bili Reservoir in accordance with storage capacity. Evaluation by analyzing the reservoir performance which includes reliability, resilience and vulnerability in existing conditions. Optimization using a dynamic program with an objective function to minimize the relative difference between target and release. Based on results of analysis, performance optimized operating rule is better than performance existing operating rule. In existing conditions, reliability of reservoir is obtained to supply water needs 71,66%, maximum deficit ratio is 80% with Tgagal 10,2 periods, vulnerability is 76% and water deficit value in water supply needs 2741,33 million m3. After optimization reservoir, reliability increased to 94,79%. This means that reservoirs can water supply up to 23,13% greater than reliability existing reservoirs. Value of resilience in optimization reservoir operation is 0,17 and maximum deficit ratio 42%. Tgagal value is 5,83 periods and amount of water deficit in serves reservoir is 515,7 million m3.